The impact of banning mobile phones in Swedish secondary schools - Dany Kessel; Hulda Lif Hardardottir; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2019)
Recently, policy makers worldwide have suggested and passed legislation to ban mobile phone use in schools. The influential and only quantitative evaluation by Beland and Murphy (2016), suggests that this is a very low-cost but effective policy to improve student performance. In particular, it suggests that the lowest-achieving students have the most to gain. Using a similar empirical setup but with data from Sweden, we partly replicate their study and thereby add external validity to this policy question. Furthermore, we increase the survey response rate of schools to approximately 75 % compared to 21 % in B&M, although at the expense of the amount of information collected in the survey. In Sweden, we find no impact of mobile phone bans on student performance and can reject even small-sized gains.
Keywords: I21; I28; O33; J24; 330; Mobile phone ban; Student performance